2013
DOI: 10.1177/1040638713498600
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem stability of S100B in the aqueous humor of northern fur seals (Callorhinus ursinus)

Abstract: Bycatch (accidental drowning in fishing nets) is a significant problem for some marine mammal species, but can be difficult to diagnose as there are no pathognomonic gross or histological lesions. In human medicine, biomarkers such as S100B are increasingly being used to investigate hypoxic-ischemic syndromes, but, to the authors’ knowledge, studies using this marker have not been reported for marine mammal species. The aims of the current study were to determine baseline postmortem S100B levels in a pinniped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…However, this study has also shown the importance of doing prospective systematic standardized necropsies in both stranded and bycaught marine mammals, and the importance of recovery of fresh stranded and bycaught animals. Future studies with larger sample sizes for pinnipeds and cetaceans, as well as different fishing gear, may contribute to a better understanding of speciesand gear-specific markers, in addition to searching for new PUE findings or markers (Roe et al 2013). In turn, this knowledge could be used to recommend changes in gear or techniques to mitigate bycatch.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study has also shown the importance of doing prospective systematic standardized necropsies in both stranded and bycaught marine mammals, and the importance of recovery of fresh stranded and bycaught animals. Future studies with larger sample sizes for pinnipeds and cetaceans, as well as different fishing gear, may contribute to a better understanding of speciesand gear-specific markers, in addition to searching for new PUE findings or markers (Roe et al 2013). In turn, this knowledge could be used to recommend changes in gear or techniques to mitigate bycatch.…”
Section: Discussionmentioning
confidence: 99%